The effectiveness of Wordwall and Macromedia Flash on ProblemBased Student Learning Outcomes on Acids-Bases - Imelda Prisilia Sinuhaji; Ani Sutiani (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2025)
Quality education requires a learning system that can develop the potential of students, one of which is through the development of effective learning media and models. However, in practice, learning media are often not used, learning models are monotonous, students' problem-solving abilities are low, and student activities are passive, resulting in low learning outcomes, especially in acid-base material. This study aims to determine the significant differences in learning outcomes between students using Wordwall and Macromedia Flash problem-based media on acid-base material in grade XI, as well as to assess the effectiveness of both media. The research method employed purposive sampling with a Two Group Pretest-Posttest design. Data were collected through cognitive learning achievement tests and analyzed using the Kolmogorov-Smirnov normality test, Levene's test for homogeneity, two-tailed t-test, two-way ANOVA, and N-Gain test with SPSS 26.0. The results of the study indicate that the learning outcomes of students using the Macromedia Flash media with the problem-based learning model were higher than those using the Wordwall media onacid-base material